The effects of corn- or sorghum-based diets with or without sorghum dried distillers grains with solubles on lactating sow and litter performance - Sotak, K.M.; Goodband, Robert D.; Tokach, Michael D.; DeRouchey, Joel M.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
A total of 140 sows (PIC 1050) and their litters were used to determine the effects of corn- or sorghum-based diets with or without 20% sorghum dried distillers grains with solubles (DDGS) on lactating sow and litter performance. On d 110 of gestation, sows were allotted to 1 of 4 dietary treatments arranged in a 2 × 2 factorial with main effects of grain source (corn vs. sorghum) and sorghum DDGS (0 vs. 20%; 32.1% CP and 9.2% crude fat as-fed). All diets were formulated to 0.97% standardized ileal digestible lysine but were not balanced for energy. Litters were equalized to at least 12 pigs per sow after farrowing. Two sows and one sow were removed from the study for the sorghum and sorghum-DDGS treatments, respectively, because of initial feed refusal.
Keywords: Swine; Lactation; Sorghum; Sorghum DDGS; Sow